A Clinical Study on Rheumatoid Arthritis with Reference to Ultrasonographic Evidence of Synovitis for Early Diagnosis - Hazarika, Sarat Chandra; R Marak, Rebecca; Brahma, Kabita; Nath, Lipee; Baruah, Jishnu Prakash (Journal of Neonatal Surgery, 2025)
Objectives: Early rheumatoid arthritis has been defined as a disease duration of 24 months or less, with a focus on the first 6 to 12 months. Ultrasound technology is more sensitive and accurate in the diagnosis of rheumatoid synovitis. The objective of this study is to assess ultrasonographic evidence of synovitis. Methods: This hospital based, observational, single centre study was carried in 70 patients of rheumatoid arthritis taken from Rheumatology, Medicine and Orthopedics OPD or admitted in Medicine Department of Assam Medical College & Hospital from July 2021 to June 2022. The statistical analysis of data was performed using the computer program, statistical package for Social Sciences. Results: The mean age of study population is 44.84±14.38 years. The maximum number of patients seen in the 41-50 age group. The male to female ratio was 1:3.67. Out of 70 patients rheumatoid factor was positive in 40(57.14%). Fifty two (74.29%) patients were having disease duration of <10years.Out of 1960 joints screened,1117(57%) joints showed synovial hypertrophy on the ultrasound grey scale. In the power doppler scan, 940(47.9%) joints had power doppler signal. In comparison between clinical joint involvement and joints with power doppler signal 23.37% had power doppler signal. 268 (26.54%) joints from the clinically nil group had synovial hypertrophy on grey scale ultrasound. Conclusion: MSUS in rheumatoid arthritis helps in detection of subclinical synovitis which are not evident in conventional clinical examination and thus helps in treatment and prediction of disease relapse and structural progression.